1998
DOI: 10.1002/(sici)1520-636x(1998)10:4<307::aid-chir4>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of racemization of (+)- and (?)-diethylpropion: Studies in aqueous solution, with and without the addition of cyclodextrins, in organic solvents and in human plasma

Abstract: The configurational stability of (+)‐ and (−)‐diethylpropion [(+)‐ and (−)‐2‐(diethyl)‐1‐phenyl‐1‐propanone or (+)‐ and (−)‐DEP] was investigated systematically from chemical, pharmaceutical, and pharmacological aspects. The enantiomeric ratio was monitored directly with a recently developed stability‐indicating enantioselective HPLC method. In aqueous solutions, the rate of racemization increased non‐linearly with increasing pH and with increasing phosphate buffer concentration. The racemization rate showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[37] Amfepramone( 11,T able 4) racemisation rates werem easured over ap Hr ange of 5.5 to 8a nd with varying phosphate buffer concentrations (as well as in human plasma). [38] Racemi-sation rate constants increased with increasing pH and with increasing buffer concentrations, butn either increase was linear.T here is no obvious site for equilibrium deprotonation, making general-base catalysis resulting from rate-determining deprotonation the most likely mechanism for racemisation. This interpretation does not explain the non-linear behaviour,h owever.C ompound 11 might also undergo equilibrium protonation on the nitrogen, followed by rate-determining deprotonation of the stereogenic centre.…”
Section: General-base Catalysismentioning
confidence: 91%
See 1 more Smart Citation
“…[37] Amfepramone( 11,T able 4) racemisation rates werem easured over ap Hr ange of 5.5 to 8a nd with varying phosphate buffer concentrations (as well as in human plasma). [38] Racemi-sation rate constants increased with increasing pH and with increasing buffer concentrations, butn either increase was linear.T here is no obvious site for equilibrium deprotonation, making general-base catalysis resulting from rate-determining deprotonation the most likely mechanism for racemisation. This interpretation does not explain the non-linear behaviour,h owever.C ompound 11 might also undergo equilibrium protonation on the nitrogen, followed by rate-determining deprotonation of the stereogenic centre.…”
Section: General-base Catalysismentioning
confidence: 91%
“…[65] Liquid chromatographic techniques, such as chiral HPLC, are used widely for studying stereochemistry and racemisation. [33,38,50,88] Typical approaches involve either full separation of the enantiomerso rp eak shapea nalysisf or compounds racemising in the HPLCe luent. [10,89] Al iquid-chromatography methodh as been adapted to include an artificial membrane intendedt om imic cell membranes, an environment that many drugs partitioni nto.…”
Section: Experimental Techniques For Studying Racemisationmentioning
confidence: 99%
“…The partial racemization of the above cited drug was reported with aminoalcohols as free base for the corresponding esters and no racemization was reported with aminoalcohols as hydrochloride salts. 50 Mey et al 51 reported 23-25 min as half life of racemization for (þ)-and (À)-diethylpropion (DEP) in human plasma. Tumambac et al 52 reported half life of 2-benzoylcylohexanone in hexanes and ethanol as 552 and 23.8 min respectively at 668C.…”
Section: In Vitro Racemizationmentioning
confidence: 99%
“…The authors described a rapid racemization in many solvents and in dog and human plasma. Mey et al 51 studied the kinetics of racemization of (þ)-and (À)-diethylpropion (DEP) and reported that on increasing pH and phosphate buffer concentration, the rate of racemization increased in aqueous solution but in cyclodextrins (CDs), the racemization rates of the enantiomers of DEP did not vary so much.…”
Section: Effect Of Different Variables On Racemizationmentioning
confidence: 99%